URBAN AND RURAL DIMENSIONS OF THE ROLE OF EDUCATION IN INCOME INEQUALITY IN BANGLADESH. Issue 3 (14th January 2019) - Mahmud, Shaikh Shahriar; Akita, Takahiro
Abstract : Using the 2005 and 2010 National Household Income and Expenditure Surveys, this study examines the urban and rural dimensions of the role of education in income inequality in Bangladesh. The government needs to expand the access to and the quality of primary education because a large proportion of citizens are uneducated. This would reduce not only the urban–rural educational gap but also the educational inequalities within urban and rural areas. As the income disparity between urban–rural and educational groups is small and more than 90% of overall income inequality is the result of inequalities within educational groups, the government needs to introduce policies that could reduce inequalities within such groups. In urban areas, policies to help reduce skill mismatches in the labor market are required, while non‐agricultural employment may need to be promoted to mitigate rural income inequality.